Day 2 Tue, February 21, 2017 2017
DOI: 10.2118/182638-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Unstable Water Floods and Tertiary Polymer Floods into Highly Viscous Oils

Abstract: The saturation distribution after unstable water flooding into highly viscous oil may have a decisive impact on the efficiency of tertiary polymer flooding, in particular due to hysteresis effects associated with oil banking. In this work, we model water flood and tertiary polymer flood experiments performed on Bentheimer sandstone slabs with heavy oils of about 2000 cP and 7000 cP, and compare the numerical results with experimental production, pressure and X-ray data. The unstable water floods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At breakthrough, the subnetwork { NW } B becomes connected (in the sense discussed in sections 2.1 and 2.2) and can be compared to { R c } and { Q c }. To validate our computer code, we simulated the waterflooding experiment reported in de Loubens et al (2018) and compared our result to de Loubens et al's X‐ray image of the waterflooded pore space at breakthrough as well as their 2‐D dynamic network simulation. We found that the simulated injection pattern was in good qualitative agreement with de Loubens et al's experimental and simulation results (see supporting information section S5).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…At breakthrough, the subnetwork { NW } B becomes connected (in the sense discussed in sections 2.1 and 2.2) and can be compared to { R c } and { Q c }. To validate our computer code, we simulated the waterflooding experiment reported in de Loubens et al (2018) and compared our result to de Loubens et al's X‐ray image of the waterflooded pore space at breakthrough as well as their 2‐D dynamic network simulation. We found that the simulated injection pattern was in good qualitative agreement with de Loubens et al's experimental and simulation results (see supporting information section S5).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The capillary pressure curves included in the sensitivity analysis are given in Figure 19. The primary drainage curve is obtained from de Loubens et al 36 The forced imbibition curves for water and polymer are obtained from unpublished laboratory work conducted at Uni Research CIPR, Norway.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Fingering has been observed to occur at all scales ranging from the phases by-pass at pore level [16] to the phases partitioning at reservoir level, causing severe early waterbreakthrough. The magnitude of their dimensions variation causes its modelling to be a perilous task using Darcy's scale models [17]. A possible alternative is to upscale flow dynamics properties from laboratory experiments, to account for the complexity of these flows at higher scale resolution [18].…”
Section: Introductionmentioning
confidence: 99%
“…Still they are by nature limited in dimensions and connectivity [20,22]. Slab experiments conducted on Bentheimer samples have allowed to look further in the 2D fingerings characterization [17,23]. However, the core width is restricted with these experiments, leading to high dimensions ratio that strongly affect the fingers growth as demonstrated by Doorwar and Mohanty in [24].…”
Section: Introductionmentioning
confidence: 99%